About the meaning of Milan Kundera's early works. - Češka, Jakub (Bohemica Olomucensia, 2023)
In a partly polemical study I raise the question of the meaning of Milan Kundera's early work. The polemic goes in two directions: first, against Jan Novák's voluminous monograph, Kundera: Czech Life and Times, and second, against Holt Meyer's summarizing review of Novák's book, which was published in French. I use the example of Novák's paraphrase of one of Kundera's early poems ("Love and Life", Man: A Wide Garden) to illustrate his fictionalizing style. By interpreting the same poem myself, I illustrate the meaning of early poetry, the knowledge of which is essential for understanding the background and dynamics of Milan Kundera's entire oeuvre. It is also centred around several basic themes. Chief among them is the theme of silencing, which is the central theme of the poem Love and Life.
Keywords: Milan Kundera; Man: A Wide Garden; Jan Novák